⎩ ⎪ ⎪ ⎨ ⎪ ⎪ ⎧ x 2 − y z = 3 7 y 2 − x z = 1 z 2 − x y = − 3 5
If x , y and z are positive numbers that satisfy the system of equations above, find the value of 1 0 0 0 0 x + 1 0 0 y + z .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
x 2 - y z = 3 7
y 2 - z x = 1
z 2 - x y = − 3 5
x 2 - y z + z 2 - x y = 2 = 2 y 2 - 2 z x
x 2 + z 2 + 2 z x = y 2 + y 2 + y z + x y
( x + z ) 2 - y 2 = y 2 + y z + x y
( x + y + z ) ( x − y + z ) = y ( x + y + z )
y =( x − y + z )
2 y = x + z
Evaluating in Original Eq.3
We get
x − z = 2
x − z = − 2
Evaluating both the Equations in Original Eq.1
We get
x = 1 3
y = 1 2
z = 1 1
When x − z = 2
And when x − z = − 2
x = − 1 3
y = − 1 2
z = − 1 1
Since x , y , and z are positive integers it cannot be negative hence it is 13 , 12 and 11 respectively
See the second equation which can be written as:
y
2
−
1
=
x
z
=
>
(
y
+
1
)
(
y
−
1
)
=
x
z
comparing LHS and RHS:
x
=
(
y
+
1
)
and
z
=
(
y
−
1
)
Use this result in any of the eq. 1 or 3 to get a quadratic eq. and solve for y.
eg. In eq.1, we get:
(
y
+
1
)
2
−
y
(
y
−
1
)
=
3
7
=
>
y
=
1
2
So,
x
=
1
3
,
y
=
1
2
,
z
=
1
1
Yours is the best and most simplest solution!
Nice tactics I like it very much
Excuse me, but how are you certain that x = y + 1 and z = y − 1 ? Another possibility could be that 1 = y − 1 and x z = y + 1 . May someone explain why the other possibility does not need to be considered?
4x3=2x6 Comparing LHS RHS: 4=2 and 3=6 😂
Log in to reply
This does not work when you have exact values, ie. in arithmetic. But, algebra is a representation. If there are two factors on LHS and RHS, if they are equal, equation will always hold true. So, maybe 4x3 not equals 2x6, but 4x3 will always be equal to 4x3. So, if axb=6x8, a=6 and b=8 will hold true. This may (or may not) hold true for other values of a and b, but, a=6 and b=8 will hold true.
⎩ ⎪ ⎨ ⎪ ⎧ x 2 − y z = 3 7 y 2 − x z = 1 z 2 − x y = − 3 5 ⟹ Summing all equations x 2 + y 2 + z 2 − x y − x z − y z = 3
⇒ 2 x 2 + 2 y 2 + 2 z 2 − 2 x y − 2 x z − 2 y z = 6
⇒ ( x − y ) 2 + ( x − z ) 2 + ( y − z ) 2 = 6
Perceive that y − z = y − x + x − z , so let´s do:
⎩ ⎪ ⎨ ⎪ ⎧ x − y = a x − z = b y − z = b − a
⇒
⎩ ⎪ ⎨ ⎪ ⎧ x − y = a ⇔ x = a + y x − z = b ⇔ z = a − b + y y − z = b − a ⇔ y − ( a − b + y ) = b − a ⇔ b − a = b − a
That shows us that x and z are in function of y .
In fact, y 2 − x z = 1 ⇔ x z = y 2 − 1 ⇔ x z = ( y + 1 ) ( y − 1 )
If it was x = y − 1 , z = y + 1 ,
( y − 1 ) 2 − y ( y + 1 ) = 3 7 ⇔ y 2 − 2 y + 1 − y 2 − y = 3 7
⇔ − 3 y = 3 6 ⇔ y = − 1 2
This is not possible because y > 0 .
So,
{ x = y + 1 z = y − 1
Thus,
( y + 1 ) 2 − y ( y − 1 ) = 3 7 ⇔ y 2 + 2 y + 1 − y 2 + y = 3 7
⇔ 3 y = 3 6 ⇔ y = 1 2 ⇔ x = 1 3 ⇔ z = 1 1
Therefore,
1 0 0 0 0 x + 1 0 0 y + z = 1 0 0 0 0 . 1 3 + 1 0 0 . 1 2 + 1 1 = 1 3 1 2 1 1
Notes :
1 ) a = 1 , b = 2 ;
2 ) ( y − 1 ) 2 − y ( y + 1 ) 2 = − 3 5 ⇔ y 2 − 2 y + 1 − y 2 − y = − 3 5
⇔ − 3 y = − 3 6 ⇔ y = 1 2 ;
3 ) y 2 − ( y + 1 ) ( y − 1 ) = 1 ⇔ y 2 − y 2 + 1 = 1 .
Subtract equation 1 and 2
(x-y)(x+y+z)= 36 (4)
Similarly, subtract equation 2 and 3
(y-z)(x+y+z)=36 (5)
Divide 4 and 5, x-y=y-z, hence x y and z are in AP
x= y-d, z=y+d, (where d =common difference)
So equation 4 becomes, yd= -12. As y is positive, d has to be negative
Substitute the value of x y and z in equation 1 and replace yd by -12, solve to get d =-1.
Hence, x=13, y=12, z=11
Problem Loading...
Note Loading...
Set Loading...
Let x = y + a and z = y + b for some real a , b . The given equations then become
(i) ( y + a ) 2 − y ( y + b ) = 3 7 ⟹ ( 2 a − b ) y = 3 7 − a 2 ,
(ii) y 2 − ( y + a ) ( y + b ) = 1 ⟹ − ( a + b ) y = 1 + a b and
(iii) ( y + b ) 2 − ( y + a ) y = − 3 5 ⟹ ( 2 b − a ) y = − 3 5 − b 2 .
Adding these equations together yields that
0 = 3 − ( a 2 − a b + b 2 ) ⟹ a 2 − a b + b 2 = 3 , (iv).
Now going back to the original equations, when we subtract the second equation from the first we find that
x 2 − y 2 − y z + x z = 3 7 − 1 ⟹ ( x − y ) ( x + y + z ) = 3 6 .
Now since we are only looking for positive solutions, we must have x > y . Similarly, subtracting the third equation from the second, we find that
y 2 − z 2 − x z + x y = 3 6 ⟹ ( y − z ) ( x + y + z ) = 3 6 .
Again, since we are looking for only positive solutions, we must have y > z . Now comparing these last two results, we see that x − y = y − z , implying that a = − b . Plugging this result ito equation (iv) yields that
a 2 + a 2 + a 2 = 3 ⟹ a 2 = 1 ⟹ a = 1 ,
since a = x − y > 0 . This in turn gives b = − 1 . Plugging these results into equation (i) yields that
3 y = 3 7 − 1 ⟹ y = 1 2 , and so x = 1 3 , z = 1 1 .
Thus 1 0 0 0 0 x + 1 0 0 y + z = 1 0 0 0 0 ∗ 1 3 + 1 0 0 ∗ 1 2 + 1 1 = 1 3 1 2 1 1 .